PEMBINAAN IRINGAN BATEL WAYANG WONG DI BANJAR PESALAKAN, DESA PEJENG KANGIN, KECAMATAN TAMPAKSIRING KABUPATEN GIANYAR - I Gusti Putu Sudarta; I Bagus Wijna Bratanatyam; I Dewa Ketut Wicaksandita (Institut Seni Indonesia Surakarta, 2024)
The Wayang Wong performance in Banjar Pesalakan is a form of art that has socio-religious values in its aesthetic appearances, such as dance movements, antawacana rhetoric, and Balinese gambelan instrumental show, which appear as an identity that describes the artistic creativity of the community. In a religious context, Wayang Wong is a sacred object (sesuhunan) often performed in major ceremonies in the village. As the performers of Wayang Wong age, the dynamics of aesthetic forms in performances are evolving. As part of their cultural identity, Wayang Wong expected to keep up with the changing values. In early 2023, the village's community leaders decided to gradually revitalize and re-actualize Wayang Wong performances, including improving the physical instruments and providing guidance to Wayang Wong sekaa, particularly accompanying music of the Batel Wayang Gambelan. With the proposal for revitalization and actualization by the village's leaders, the mentors through the PPKM program organized by ISI Denpasar, proposed a community service project involving lecturers and students of puppetry (pedalangan). This collaboration aims to enhance the quality of resources, including participants of Wayang Wong performance and mentors (lecturers and students). A demonstration-based empowerment method, utilizing techniques such as lectures, discussions, practices, evaluations, and performances, effectively addressed the issue through two stages. The first stage focused on training in primary instruments, such as gender wayang (Gender’s hitting techniques, gegedig, and tetekep) and kendang krumpungan (gupekan, mupuh kendang, and kekendangan/drumming patterns). Second, it combines all instruments through practices of various tabuh (rhythmic patterns) of gendhing in Wayang Wong performances.